METHOD PARAMETER OPTIMIZATION ROCK CRUSHING. - Yu. A. Chpurgalov; M. Yu. Chpurgalova (Системный анализ и прикладная информатика, 2015)
Set of parameters characterizing the process of interdependence rock crushing and the technique of joint optimization of the above parameters. Recommendations for use of the algorithm in the workplac